Peran Sumber Daya Manusia, Pendidikan, dan Kebijakan Pemerintah dalam Meningkatkan Pertumbuhan Ekonomi Indonesia - Devi Prameswati; Fikria Hanifa Nabiha; Flira Tri Octaviani; Puri, Gista Alfania; Kayla Aryani Putri Nugroho; Ahmad Setiawan Nuraya (Dharma Ekonomi, 2025)
The study was conducted to analyze the relationship between the quality of human resources (HR) and economic growth in Indonesia which aims to determine the role of Human Resources, Education, and Government Policy in Indonesia's economic growth. By using descriptive qualitative research methods, data were collected through literature studies by collecting journals and articles spread across the Internet. The results of the study obtained were that 1) The Role of Human Resources in Economic Growth. 2) The Role of Education in Economic Growth. 3) The Role of Government Policy in Economic Growth. Based on the results of the study, it is expected that the government can continue to improve the quality of education and HR skills to improve the Indonesian economy.